COVID-19: Role of Ambulatory Surgery Facilities in This Global Pandemic - Rajan, Niraja (Anesth Analg, 2020)
Coronavirus Disease 2019 (COVID-19) has now become a global pandemic. This has led the United States to declare a national emergency and resulted in a ban on all elective diagnostic and therapeutic procedures as well as elective surgery in inpatient and outpatient settings. Ambulatory surgery facilities (ASF) that perform only elective procedures are thus likely to be closed. However, these facilities may be able to assist acute care hospitals as essential (urgent and emergent) surgeries and diagnostic and therapeutic procedures will still need to be performed. The aim of this article is to explore the potential contribution of ASFs in the current health care crisis. It is important to understand that COVID-19–related information is continually evolving, and thus, the discussion provided here is subject to change.